(Not) in my backyard? The impact of citizen initiatives on housing supply in Germany - Thorsten Martin; Felix Arnold; Ronny Freier (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
We examine the effect of citizen initiatives on finished residential area in the German federal state of Bavaria. There is already a prominent literature on the fiscal effect of initiatives and political economic reasons that drive urban development. Yet, there is almost no literature that links the effect of citizen participation to local land use patterns. This paper attempts to fill this gap. By using neighboring initiatives as an instrument for the occurrence of an initiative in a given municipality, we identify a negative impact of initiatives on finished residential area per capita. Evaluated at the mean, this effect amounts to about 10% regarding the finished residential area per capita. This effect takes place five to nine years after the initiative was conducted.
Keywords: D72; Q15; R52; 330